Using Extensive and Intensive Reading to Improve Reading Comprehension in English Language Learners (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the complementary roles of extensive and intensive reading in enhancing reading comprehension among English language learners (ELLs). It defines both approaches: extensive reading as reading large amounts of easier texts for overall understanding and enjoyment, and intensive reading as close, analytical reading of shorter, more challenging texts. The article highlights the benefits of extensive reading, including vocabulary acquisition, reading fluency, and learner motivation, while also emphasizing that intensive reading supports deeper understanding of grammar, vocabulary usage, and critical reading skills. The author argues that integrating both methods creates a more balanced and effective reading curriculum. Practical strategies are provided for classroom implementation, such as graded readers, reading journals, vocabulary tasks, and discussion activities. The article concludes that a combined approach fosters both reading fluency and accuracy, ultimately leading to improved overall comprehension in ELLs.